Networks of Modernity Germany in the Age of the Telegraph, 1830-1880 - Johnston, Jean-Michel (Oxford University Press, 2021)
This book offers a fresh perspective on the history of Germany by investigating the origins and impact of the 'communications revolution' that transformed state and society during the nineteenth century. It focuses upon the period 1830-80, exploring the interactions between the many different actors who developed, administered, and used one of the most important technologies of the period-the electric telegraph. Drawing upon evidence from Prussia, Bavaria, Bremen, and a number of towns across Central Europe, it reveals the channels through which knowledge circulated across the region, stimulating both collaboration and confrontation between the scientists, technicians, businessmen, and bureaucrats involved in bringing the telegraph to life. It highlights the technology's impact upon the conduct of trade, finance, news distribution, and government in the tumultuous decades that witnessed the 1848 revolutions, the wars of unification, and the establishment of the Kaiserreich in 1871. Following the telegraph lines themselves, it weaves together the changes which took place at a local, regional, national, and eventually global level, revisiting the technology's impact upon concepts of space and time, and highlighting the importance of this period in laying the foundations for Germany's experience of a profoundly ambiguous, networked modernity.